No evidence of SARS‐CoV‐2 transmission through transfusion of human blood products: A systematic review. Issue 3 (19th July 2021) - Mawalla, William Frank; Njiro, Belinda J.; Bwire, George M.; Nasser, Ahlam; Sunguya, Bruno
Abstract: The presence of viral nucleic material in the circulation poses a theoretical risk of transmission through transfusion. However, little is known about the possibility of the actual transmission through transfusion or transplantation of blood products. A PROSPERO registered systematic review pooled evidence from PubMed/MEDLINE, Google Scholar and CINAHL. The search included studies on severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) transmission through human blood products. In total 537 studies were extracted, and only eight articles (1.5%) were eligible for the final analysis. A total of 14 patients received blood products from coronavirus disease‐2019 (COVID‐19) virus‐positive donors, and six (42.9%) tested negative for COVID‐19 RT‐PCR for up to 14 days post‐transfusion/transplantation. There were no documented clinical details on the COVID‐19 test for eight (57.1%) blood products recipients. Of the eight patients, none of them developed any COVID‐19‐related symptoms. In conclusion, there is limited evidence of transfusion transmission of SARS‐CoV‐2 via human blood products. Consolidation of further evidence, as it emerges, is warranted.